Assessment of nutritional change processes and their relationship with macronutrient intake and anthropometric measurements in adults - Seker, Beyza Nur; Kocatepe, Neslihan; Bayraktar, Damla Zeynep; Seven Avuk, Hande (Frontiers in Nutrition, 2026)
BackgroundThis study assessed the relationship between adults' nutritional behavior change process and their diet implementation, energy, macronutrient intake, and anthropometric measurements.MethodsThis cross-sectional study was conducted with 400 adults (50% men, 50% women, median age 27 years). A face-to-face questionnaire including sociodemographic information, smoking status, diet experience, and the Nutritional Change Processes Scale (NCPS) was applied. Food consumption was recorded using a 24-hour recall method, and anthropometric measurements were taken.ResultsAmong participants, 50.5% were classified as underweight-normal, 33.5% as overweight, and 16% as obese, while 37.8% had past dieting experience. Those with a dieting history had significantly higher NCPS scores [110 (52–192)] than those without [77 (48–176); p < 0.001]. The NCPS score of obese participants [113.50 (52–192)] was the highest compared to underweight-normal [79.50 (48–177)] and overweight [90.5 (48–176)] participants (p < 0.001). A positive correlation was found between total NCPS score and body weight, BMI, and body fat percentage (r = 0.200, p < 0.001; r = 0.355, p < 0.001; r = 0.161, p = 0.001, respectively). A negative correlation was observed with energy intake, carbohydrates, and carbohydrate percentage (r = −0.132, p = 0.008; r = −0.165, p = 0.001; r = −0.158, p = 0.002, respectively). However, in multivariable analyses, the association between BMI and NCPS was no longer significant after adjustment for age and gender, and was significantly influenced by energy intake (p < 0.05).ConclusionThis study shows that obesity and past dieting experiences are associated with higher involvement in dietary behavior change processes, but this relationship is significantly influenced by age, gender, and energy intake. Furthermore, the finding that high awareness does not guarantee balanced macronutrient intake underscores the need for multidimensional weight management strategies that address both individual cognitive factors and environmental determinants.